The early stages of mate selection - LI, Norman P. (Institutional Knowledge at Singapore Management University, 2023)
Given the centrality of mating and reproduction in the long course of human evolution, the selection of mates is a critical adaptive challenge that humans have needed to successfully confront throughout evolutionary history. This chapter provides an overview of major evolutionary theories of human mating, describes key hypotheses of mate preference psychology, and reviews relevant empirical research for the early stages of mate selection. We discuss mate preference adaptations for selecting both long-term and short-term mates, as well as methodological issues, controversies, and other developments that have, in recent years, surfaced in the mate-selection literature.